The Opening Hand: British Intelligence, Archives, and the End of the Cold War - Horrall, Andrew (Archivaria, 2002)
This essay reviews Stella Rimington’s Open Secret: The Autobiography of the Former Director-General of MI5, and Richard J. Aldrich’s The Hidden Hand: Britain, America and Cold War Secret Intelligence. Since unsuccessfully trying in 1987 to block the publication of Spycatcher, Peter Wright’s memoirs of his career in British intelligence, the British government has been increasingly tolerant towards revelations about the secret services. The end of the Cold War has fostered this climate of official openness. As a result, in 1997, the British intelligence agency MI5 began transferring historic files to the Public Record Office in London. Rimington’s memoirs and Aldrich’s history, based in part on newly available documents, are examples of the boundary between what the British government is willing to release to archives, and the information that it feels must still remain secret. RÉSUMÉ L’auteur fait la critique des ouvrages Open Secret: The Autobiography of the Former Director-General of MI5, de Stella Rimington et de The Hidden Hand: Britain, America and Cold War Secret Intelligence, de Richard J. Aldrich. Après avoir sans succès essayé d’empêcher la publication de Spycatcher, les mémoires de l’agent secret Peter Wright en 1987, le gouvernement britannique a été de plus en plus tolérant quant aux révélations au sujet de ses services secrets. La fin de la guerre froide a encouragé ce climat d’ouverture officielle et permis, en 1997, le début du transfert des dossiers historiques de l’agence secrète britannique M15 au Public Record Office de Londres. Les mémoires de Rimington et l’histoire de Aldrich, basés en partie sur des documents nouvellement disponibles, sont des exemples de la frontière entre ce que le gouvernement britannique veut bien transmettre aux archives et ce qu’il préfère garder secret.